Hybrid-drug design targeting pseudomonas aeruginosa DHPS and DHFR - Jayaraman, Premkumar (2014)
In this study, we successfully present the dual-target design hypothesis to inhibit both dihydropteroate synthase (DHPS) and dihydrofolate reductase (DHFR) enzymes using a novel scheme that integrates our previous antibiotic-phytochemical interaction data, fragment combination and knowledge-based methods. Both the enzymes are well established antibacterial targets from folate biosynthesis pathway and their synergistic modulation by a single hybrid entity may have profound therapeutic benefits. Evaluation of the designed hybrid compounds based on their physico-chemical properties has indicated them as promising drug candidates with drug-like pharmacotherapeutic profiles. In addition, the stereo-electronic properties such as HOMO, LUMO and MEP maps calculated by quantum chemical methods gave a good correlation with the common pharmacophoric features required for dual-site interactions. Furthermore, docking and dynamics simulation studies reveal that the designed hybrid compounds have favorable binding affinity and stability in both pterin-binding site of DHPS and folate-binding site of DHFR by forming strong hydrogen bonds and hydrophobic interactions with key active-site residues. Looking forward this study could serve as a prospective lead in the process of new natural-product based hybrid-drugs development.